ANALISIS SISTEM PENGENDALIAN MANAJEMEN DALAM PERSEDIAAN BAHAN BAKU PADA GULA KACANG CAP WARDAH - Febriningtias, Lintang; Fauziah, Rahma Adibatul; Utomo, Budi (COMPETITIVE, 2021)
Raw material inventory management control system is important in planning production needs. This study discusses the comparison between raw material inventory control using the EOQ method with company policies. Inventory control will incur costs including ordering costs, purchasing costs, maintenance costs, and storage costs. This study aims to analyze the optimal amount of peanut sugar raw material needed by Wardah Home Industry per 2019 period, the total cost of peanut sugar raw material inventory that must be incurred by Wardah Home Industry, the right time to reorder peanut sugar raw materials, large the ideal stock security that Wardah Home Industry must provide for the 2019 period. This research was conducted using descriptive research with a quantitative approach. The results show that the calculation using the EOQ method can help save the company's costs compared to the policies carried out by the company. Calculations carried out include calculating the frequency of purchasing raw materials, quantity of safety stock (safety stock), reorder time (reorder point), and calculation of total inventory cost (total inventory cost).